P.013 Needs assessment of rural telemedicine care for Parkinson disease in British Columbia. (June 2019) - Peacock, DJ; Baumeister, PA; Monaghan, A; Siever, JE; Wile, D
Abstract : Background: People with Parkinson disease (PD) face progressive mobility loss, but medical treatment is dependent on clinical assessment and examination. Regional patient and physician density patterns pose further problems to accessing care. Telehealth may improve access particularly among rural populations, but an approach to this problem should consider patient perspectives. Methods: We surveyed and conducted a focus group for people with PD and their caregivers. Questions assessed perceptions of barriers to neurological care and use of telehealth for PD management. Thematic analysis was performed to classify qualitative data. Results: 18 individuals completed the survey and 7 parties joined the focus group. 52% of participants travel >50km for neurologist appointments (range = 59 to 842km). Perceived barriers include cost and difficulty of travel, wait times, lack of interdisciplinary healthcare and deep brain stimulation outside large cities. 80% of participants (95% C.I. 64-96%) would likely or very likely use telehealth for follow-up neurologist appointments if proven as good as in-office visits. Participants associated telehealth with improved quality of care, improved access to care, and cost savings. Conclusions: This sample of people with PD and their caregivers report willingness to access care via telehealth to reduce perceived cost and travel for specialty care.